An Inner Warp in the Doar 44 T Tauri Transition Disc - Rannou-Fuentes, F; Roman-Asenjo, P; Carcamo-Vasquez, M (Oxford University Press, 2018)
Optical/IR images of transition discs (TDs) have revealed deep intensity decrements in the rings of HAeBes HD 142527 and HD 100453 that can be interpreted as shadowing from sharply tilted inner discs, such that the outer discs are directly exposed to stellar light. Here we report similar dips in SPHERE+IRDIS differential polarized imaging (DPI) of T Tauri DoAr 44. With a fairly axially symmetric ring in the sub-mm radio continuum, DoAr 44 is likely also a warped system. We constrain the warp geometry by comparing radiative transfer predictions with the DPI data in H band (Qϕ(H)) and with a re-processing of archival 336 GHz ALMA observations. The observed DPI shadows have coincident radio counterparts, but the intensity drops are much deeper in Qϕ(H) (∼88 per cent), compared to the shallow drops at 336 GHz (∼24 per cent). Radiative transfer predictions with an inner disc tilt of ∼30 ± 5 deg approximately account for the observations. ALMA long-baseline observations should allow the observation of the warped gas kinematics inside the cavity of DoAr 44. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society